(untitled) (Research, Society and Development, 2022)
The term cancer encompasses more than 100 types of malignancy that can affect different organs. It is characterized by a disordered growth of cells capable of invading adjacent tissues or distant organs. Scientific evidence has shown the benefits of meditation combined with conventional treatment. The present study aimed to investigate the influence of meditation on the control of vital signs in cancer patients sheltered in a charity house in the municipality of Vitória da Conquista, Bahia. This is a quantitative research, of the action-research type that promoted the use of meditation as a complementary integrative practice in 48 cancer patients. The results showed that it was possible to influence the control of the participants’ vital signs through meditation. It is concluded that meditation is configured as an important supporting technique in the treatment of cancer patients; however, the present study has limitations in terms of collection time and sample size, which raises the need for further studies on this topic in the scientific community.